The Influence of Principal Leadership, Work Motivation, and Work Discipline on Teacher Performance - Sucipto, Afan; Handayani, Yuniorita Indah; Dimyati, Muhaimin (PT. AHS Konsultan dan Pelatihan, 2024)
Teachers performance is an activity shown by a teacher carrying out his work. Problems in teacher performance are new teachers who are not from education, national exam scores which always decline every year and teachers who do not teach according to their abilities. In this study, the factors that are suspected to influence teacher performance are the principal's leadership, work motivation and work discipline. The aim of this study was to determine whether there was an influence between the leadership of the school principal, work environment, work motivation and work discipline on the performance of the SMA Darussalam Blokagung teachers. The population in this study was 45 teachers of SMA Darussalam Blokagung. This research is a population study, which means used the entire number of teachers at SMA Darussalam Blokagung. The method used in this research is percentage descriptive statistics and multiple linear regression analysis by distributing questionnaires. This study shows that principal leadership has a positive and significant influence on teacher performance at SMA Darussalam Blokagung. Work motivation also plays an important role in improving teacher performance, both in terms of intrinsic and extrinsic motivation. Work discipline has been shown to contribute to teacher effectiveness in managing classes and carrying out their professional duties. Overall, leadership, work motivation, and work discipline together create a more productive learning environment and improve student learning outcomes.